Engineered defect-rich TiO2/g-C3N4 heterojunction: A visible light-driven photocatalyst for efficient degradation of phenolic wastewater. (January 2022) - Qu, Xiao; Chen, Chuntao; Lin, Jianbin; Qiang, Wei; Zhang, Lei; Sun, Dongping
Abstract: Photocatalytic technology has been considered as an effective way for pollutants removal. Considering that the nature of the photodegradation of pollutants is the free radical reaction on the surface of the catalyst, promoting the generation of free radicals is a direct and effective way to facilitate the mineralization of pollutants. Unfortunately, the shortcomings strongly limit its photocatalytic activity such as insufficient sunlight utilization, small catalytic surface and rapid recombination of charge. Here, a heterostructure of defect-rich TiO2 nanoparticles anchored in g-C3 N4 was fabricated by a synchronous compound process. This heterostructure (4TiO2 /g-C3 N4 ) exhibits an enhanced visible light absorption due to its narrow band gap energy of 2.27 eV. Therefore, it possesses an outstanding photocatalytic activity for the degradation of phenol (1.63 × 10 2  μmol g −1 h −1 ), p -nitrophenol (1.15 × 10 2  μmol g −1 h −1 ), o-cresol (1.43 × 10 2  μmol g −1 h −1 ) and p-cresol (1.45 × 10 2  μmol g −1 h −1 ). The calculated quantum yields of 4TiO2 /CN for pollutants degradation are 1.29 × 10 −6 for phenol, 9.10 × 10 −7 for p -nitrophenol, 1.14 × 10 −6 for o-cresol and 1.15 × 10 −6 for p-cresol, respectively. By utilizing the periodic topology of MOFs, this work provides an improved approach for constructing TiO2 /g-C3 N4 heterojunctions with enhanced degradation of robust organic pollutants. Graphical abstract: Image 1 Highlights: Heterojunction of oxygen deficient TiO2 confined in g-C3 N4 nanosheets was prepared. High phenols photodegradation was performed with TiO2 /g-C3 N4 catalyst. TiO2 /g-C3 N4 shows reusability and stability for treatment of phenolic wastewater.